The Cyrillic and Serbian culture - Tanasić, Sreto (Napredak, 2023)
The paper speaks about the place and importance of the Serbian Cyrillic in Serbian culture. The Cyrillic with the Serbian language is undoubtedly among the most important identity signs, which proves that it is also necessary to assign such importance to it when devising national and cultural policies. It is exactly due to such identity importance that the Cyrillic was suppressed from the Serbian nation in the past and it continued in the 20th century, еspecially after the Second World War. Even today, after the breakup of the Serbian-Croatian language unity, many powers have an organized way of trying to prevent the return of the Cyrillic to its place. That speaks about its importance for the Serbian cultural and national identity.